The procoagulant potential of environmental particles (PM10). Issue 3 (21st February 2005) - Gilmour, P S; Morrison, E R; Vickers, M A; Ford, I; Ludlam, C A; Greaves, M; Donaldson, K; MacNee, W
Abstract : Background and Aims: Epidemiology studies have shown that cardiovascular (CV) disease is primarily responsible for the mortality associated with increased pulmonary environmental particle (PM10 ) exposure. The mechanisms involved in PM10 mediated CV effects are unknown although changes in plasma viscosity and in the homoeostasis of blood coagulation have been implicated. It was hypothesised that PM10 exposure would result in an inflammatory response and enhance the activation of the extrinsic coagulation mechanisms in pulmonary and vascular cells in culture. Methods: Primary human monocyte derived macrophages and human umbilical cord vein endothelial, human alveolar type II epithelial (A549), and human bronchial epithelial (16HBE) cells were tested for their inflammatory and procoagulant response to PM10 exposure. IL-8, tissue factor (TF), and tissue plasminogen activator (tPA) gene expression and protein release, and coagulation enhancing ability of culture media were determined 6 and 24 hours following exposure. Results: The culture media from macrophages and 16HBE bronchial epithelial cells, but not A549 cells, exposed to PM10 had an enhanced ability to cause clotting. Furthermore, H2 O2 also increased the clotting activity. Apoptosis was significantly increased in macrophages exposed to PM10 and LPS as shown by annexin V binding. TF gene expression was enhanced in macrophages exposed to PM10, and HUVEC tissue factor and tPA gene and protein expression were inhibited. Conclusions: These data indicate that PM10 has the ability to alter macrophage, epithelial, and endothelial cell function to favour blood coagulation via activation of the extrinsic pathway and inhibition of fibrinolysis pathways.